2007
DOI: 10.1111/j.1365-2141.2007.06608.x
|View full text |Cite
|
Sign up to set email alerts
|

Leukaemia‐related gene expression in bone marrow cells from patients with the preleukaemic disorder Shwachman–Diamond syndrome

Abstract: SummaryShwachman-Diamond syndrome (SDS) is an inherited bone marrow failure disorder with cytopenia and a high propensity for myelodysplastic syndrome (MDS) and leukaemia, particularly acute myeloid leukaemia. The mechanism of leukaemogenesis in SDS is unknown. In accordance to the multi-hit theory of carcinogenesis, it is likely that several molecular and cellular hits occur before MDS/leukaemia become apparent. This study used oligonucleotide microarray to identify gene expression patterns, which were shown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 44 publications
2
30
0
Order By: Relevance
“…1 Analysis of critical genetic regulators of normal hematopoiesis has identified that constitutional or acquired inactivating mutations of such genes may contribute to bone marrow failure syndromes, myelodysplastic syndromes, and/or hematopoietic neoplasms. [2][3][4] Despite advances in whole-genome analysis, the underlying genetic events that contribute to many hematopoietic disorders remain unclear, and innovative gene-discovery approaches are needed to deepen our understanding of hematopoietic development in order to design more effective and specific therapeutic approaches to treating hematopoietic diseases.In recent years, the zebrafish (Danio rerio) has emerged as an excellent animal model system for studying the genetic pathways of vertebrate development. 5 The combined genetic and embryologic advantages of the zebrafish are ideal for studying organogenesis and, in particular, hematopoiesis.…”
mentioning
confidence: 99%
“…1 Analysis of critical genetic regulators of normal hematopoiesis has identified that constitutional or acquired inactivating mutations of such genes may contribute to bone marrow failure syndromes, myelodysplastic syndromes, and/or hematopoietic neoplasms. [2][3][4] Despite advances in whole-genome analysis, the underlying genetic events that contribute to many hematopoietic disorders remain unclear, and innovative gene-discovery approaches are needed to deepen our understanding of hematopoietic development in order to design more effective and specific therapeutic approaches to treating hematopoietic diseases.In recent years, the zebrafish (Danio rerio) has emerged as an excellent animal model system for studying the genetic pathways of vertebrate development. 5 The combined genetic and embryologic advantages of the zebrafish are ideal for studying organogenesis and, in particular, hematopoiesis.…”
mentioning
confidence: 99%
“…Differential expression of genes involved in leukemia, apoptosis, and ribosome biogenesis were reported elsewhere. 10,17,25 All microarray data are available on the Gene Expression Omnibus under accession number GSE32057. …”
mentioning
confidence: 99%
“…confirmed to be higher in the bone marrow cells of a preleukemia patient, 31) and Tal-1 gene rearrangement has been observed in T-ALL patients. 32) On the basis of this knowledge, we evaluated the possibility of using the Tal-1 gene as a CT antigen candidate.…”
Section: Discussionmentioning
confidence: 75%
“…Spz1 is another bHLH transcription factor, known to be specifically expressed in the testis, that plays a role in the MAPK signaling pathway. 34,35) Tal-1 was expressed in the bone marrow as well as in the developing testis, and expression of it has been reported to be upregulated in pre-leukemic disorder, 31) suggesting that it might be a transcription regulator of commonly activated genes among spermatogenic, bone marrow, and T-ALL cancer stem cells. Several TAL-1 target genes, including tumor suppressor NKX3.1, might participate in T-ALL development.…”
Section: Discussionmentioning
confidence: 99%